Erratum (Academy of Management Journal, 1976)
A correction to the article ?Boundary Conditions for Expectancy Theory Predictions of Work Motivation and Job Performance,? by Richard Kopelman and Paul Thompson, which appeared in the June 1976 issue of the ?Academy of Management Journal,? is presented.